Sistem Monitoring dan Kontrol Motor Satu Fasa Industri Berbasis NRF24L01 - Febrika Juniar Syabilla; Wahyu; Zanu Saputra; Mahmudin (Jurusan Teknik Elektro Fakultas Teknik Universitas Bangka Belitung, 2026)
Single-phase motors are vital components in industrial infrastructure that require continuous monitoring and control systems to ensure operational availability and prevent fatal damage due to overheating or unstable mechanical loads. This research aims to design and implement a monitoring system based on wireless communication technology using the NRF24L01 module operating at a frequency of 2.4 GHz. The system is designed to monitor motor operational parameters in real-time, which include engine temperature, vibration levels, rotational speed (RPM), as well as essential electrical parameters such as voltage, current, and electricity frequency. The system architecture utilizes an ESP32 microcontroller as the main processing unit for data acquisition from various integrated sensors, which is then transmitted wirelessly via the NRF24L01 transceiver to ensure fast data delivery in industrial environments. Data integration is carried out through an efficient digital ecosystem, including the ThingSpeak platform for graphical data visualization, Google Spreadsheets for automated data archiving for long-term analysis, and the Blynk application as a remote control interface for the Variable Frequency Drive (VFD) to regulate motor speed precisely. The testing methodology was conducted in an open area environment (line of sight) to test transmission reliability and sensor accuracy. The test results show that communication using NRF24L01 can reach an effective distance of up to 220 meters. Furthermore, the system's accuracy demonstrates a very stable performance with an average error rate below 2.1%, where this error value applies consistently across all sensor parameters integrated into the system.